Konstruksi Realitas Sosial di Indonesia dalam Peran Media dan Identitas Budaya di Era Globalisasi - Pamungkas, Yudha Catur; Moefad, Agoes Moh.; Purnomo, Ryan (Metta : Jurnal Ilmu Multidisiplin, 2024)
The construction of social reality in Indonesia is heavily influenced by the interplay between mass media and social media, reflecting the evolving dynamics of globalization and local culture. This study aims to explore how media platforms shape public perceptions, cultural identity, and social norms in the Indonesian context. Employing a qualitative case study approach, the research investigates how mass media and social media frame issues and construct meanings that resonate with societal values, traditions, and contemporary challenges. Data collection involved in-depth interviews with media practitioners and users, content analysis of mass and social media materials, and participatory observation of interactions within digital communities. Analytical frameworks included Berger and Luckmann's theory of social construction, media convergence theory, and framing analysis. The findings reveal that social media platforms, such as tiktok and Instagram, facilitate a participatory culture where users blend global and local narratives, creating a hybrid reality. This hybrid reality reflects the negotiation of traditional values with modern, globalized influences, particularly in shaping the identity of younger generations. In contrast, mass media frequently aligns its framing of social issues with political and economic interests, influencing public perceptions through selective narratives. Additionally, the use of language, religious symbols, and algorithms was found to reinforce social norms and stereotypes, illustrating the media’s role in shaping societal expectations and behaviors. The study concludes that the interaction between traditional and digital media plays a significant role in constructing Indonesia’s social reality. It highlights the necessity of critically understanding media influences to navigate the complexities of identity and social dynamics in an increasingly globalized world.